Effect of calcium treatment on the browning of harvested eggplant fruits and its relation to the metabolisms of reactive oxygen species (ROS) and phenolics. Issue 10 (13th August 2021) - Ban, Qiuyan; Liu, Tongjin; Ning, Kun; Fan, Junjun; Cui, Qunxiang; Guo, Yanle; Zai, Xueming
Abstract: Eggplant is a popular vegetable in Asia; however, it has a short storage life and considerable economic losses have resulted from eggplant browning. Calcium has been reported to play a key role in the postharvest storage of plants. Here, we found that exogenous calcium application could delay eggplant fruit browning and maintain higher storage quality. The increased browning index (BI), relative electrolytic leakage (REL), and water loss were suppressed by calcium treatment during storage. Delayed browning with calcium treatment might result from a higher phenolic level and suppressed the activity of polyphenol oxidase (PPO). Less H2 O2 and O2 ‐ but more activated reactive oxygen species (ROS) scavenging enzymes accumulated in calcium‐treated fruits than in H2 O‐treated fruits. Moreover, the nonenzymatic antioxidant, ascorbic acid (AsA), was accumulated more in calcium‐treated eggplant fruits. Taken together, our data demonstrated that exogenous calcium application delayed eggplant fruit browning by regulating phenol metabolism and enhancing antioxidant systems. Abstract : 1. Calcium treatment delayed browning of eggplant fruits during storage.2. Calcium treatment maintained ROS scavenging enzyme activities in eggplant fruits during storage.